(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Is it possible in this competitive world of merit based global education, for a teacher of a school, to nurture students in a holistic pedagogy? We live in a crazy world of social media, which connects us virtually and children are losing human connectivity with self and others, dismantling their inner stability of mind. The measurement of Happiness for parents and students depends on numeric-based academic success, rather being knowledge-based. School teachers forcefully rush to complete the syllabus. Parents push their children into branded tutorial cages, which are considered to be as trump-card of success. It’s about how much you’ve earned, not what you’ve learned. The philosophies of our great visionaries like Rabindranath Tagore, Sri Aurobindo and Swami Vivekananda do exist in books of national’s curriculum, school’s almanac and educational manuals, but how far, are they instilled in a classroom pedagogy of a private or a public school teacher? Keywords holistic learning, child’s identity, language pedagogy.